Pembinaan modul pengajaran penulisan Bahasa Arab untuk pelajar Indonesia di peringkat sekolah menengah / Syarifah Rahmi - Syarifah , Rahmi (2018)
From the topic studied “THE DEVELOPMENT OF TEACHING CURRICULA OF THE ARABIC WRITING FOR INDONESIAN STUDENTS AT THE SECONDARY LEVEL” aims to determine the Arabic writing skills among student. it analyzes statistically the differences between the new method and the old method used in the new education curriculum, and finds the effectiveness of this approach due to elevate the teaching method to promote an Arabic writing as a second language. The basis used develop teaching modules is Tompkins Instructional design (7991) and it had been modified by researcher. This study is an experiment research design by using both quantitative and qualitative methods. 71 of level two student from Ruhul Islam involved in this study. They were devided into two groups: The treatment group and the control group. Collecting data was done by doing pre test, post test, questionnaires and interviewing the teachers. For the result, the researcher used statistical analysis and interpretive program SPSS (version 0202) and M. Excel. The repetition and percentage was analyzed by duplicates process in distributing the questionnaires. To answer the hypothesis, the researcher used statistical inference to test and compare the students achievement in their writing skills. Based on the analysis to the scores, there are the differences between those two groups. The average post test result is much better than pre test result. Moreover, the researcher used questionnaires and doing the interview for teachers to confirm this analysis. The student gave a positive respond using the module. It features which has an impact in improvement the learning of Arabic writing impressed them.